Osteoporosis and Osteoarthritis - Westendorf, Jennifer J.; van Wijnen, Andre J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
In Osteoporosis and Osteoarthritis expert investigators detail modern tools to enhance discovery in bone and cartilage biology and promote translational research in osteoporosis and osteoarthritis. New chapters describe methods to generate induced pluripotent stem cells, perform high-throughput chromatin analysis, assess loads on bone cells in vivo and in vitro, use state-of-the art imaging techniques to measure articular cartilage thickness and biochemical properties, and establish animal models of osteoarthritis and bone healing. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Osteoporosis and Osteoarthritis shares successful techniques that can be applied to the study of either disease.
Isolation Of Osteocytes From Mature and Aged Murine Bone -- Primary Murine Growth Plate and Articular Chondrocyte Isolation and Culture -- Isolating Endosteal Mesenchymal Progenitors From Rodent Long Bones -- Engineering Cartilage Tissue By Pellet Co-Culture Of Chondrocytes And Mesenchymal Stem Cells. - Generation Of Induced Pluripotent Stem Cells -- Profiling Histone Modifications By Chromatin Immunoprecipitation Coupled To Deep Sequencing In Skeletal Cells -- Identification Of Micrornas In Human Plasma -- Immunohistochemistry Of Skeletal Tissues -- In Vivo Axial Loading Of The Mouse Tibia -- Four Point Bending Protocols To Study The Effects Of Dynamic Strain In Osteoblastic Cells In Vitro -- Epic-µct Imaging Of Articular Cartilage -- Mouse Models Of Osteoarthritis: Surgical Model Of Post-Traumatic Osteoarthritis Induced By Destabilization Of The Medial Meniscus -- Assessment Of Knee Joint Pain In Experimental Rodent Models Of Osteoarthritis -- Induction Of Fully Stabilized Cortical Bone Defects To Study Intramembranous Bone Regeneration -- Surgical Procedures And Experimental Outcomes Of Closed Fractures In Rodent Models                                                                                                                          .
Keywords: Molecular biology; Orthopedics; Molecular Medicine; Orthopedics